Cover Image, Volume 1425, Issue 1. Issue 1 (10th August 2018) - Siddiqui, Arif J.; Molehin, Adebayo J.; Zhang, Weidong; Ganapathy, Pramodh K.; Kim, Eunjee; Rojo, Juan U.; Redman, Whitni K.; Sennoune, Souad R.; Sudduth, Justin; Freeborn, Jasmin; Hunter, Derick; Kottapalli, Kameswara R.; et al.
Abstract : On the cover : The cover image, submitted by Arif J. Siddiqui et al., is from the Original Article "Sm‐p80‐based vaccine trial in baboons: efficacy when mimicking natural conditions of chronic disease, praziquantel therapy, immunization, and Schistosoma mansoni re‐encounter, " https://doi.org/10.1111/nyas.13866 .